Do better capitalized banks lend less? Long-run panel evidence from Germany - Claudia M. Buch; Esteban Prieto (Center for Economic Studies and ifo Institute (CESifo), 2012)
Insufficient capital buffers of banks have been identified as one main cause for the large systemic effects of the recent financial crisis. Although higher capital is no panacea, it yet features prominently in proposals for regulatory reform. But how do increased capital requirements affect business loans? While there is widespread belief that the real costs of increased bank capital in terms of reduced loans could be substantial, there are good reasons to believe that the negative real sector implications need not be severe. In this paper, we take a long-run perspective by analyzing the link between the capitalization of the banking sector and bank loans using panel cointegration models. We study the evolution of the German economy for the past 60 years. We find no evidence for a negative impact of bank capital on business loans.
Keywords: G20; E50; C33; 330; bank capital; business loans; cointegration; Bank; Eigenkapital; Kreditgeschäft; Firmenkundengeschäft; Kointegration; Schätzung; Deutschland